'Pruning a genius': marginalia by Richard Dadd. Issue 2 (June 2021) - Tromans, Nicholas
After falling into mental illness as a young man, the British artist Richard Dadd (1817–86) spent some 20 years as a patient at Bethlem Hospital in London. A rare example of his writings from these years survives in the form of marginalia in a copy of Lectures on Painting and Design by Benjamin Robert Haydon, held in the Morgan Library & Museum in New York. This article presents a transcription of the notes, along with an introduction setting them in the contexts of Dadd's career and his relationship with the senior staff at Bethlem.